La comunicazione del rischio: la pandemia da COVID-19 - Mangone, Emiliana (Mediascapes journal, 2020)
The article aims to address some critical issues of risk communication by taking the COVID-19 pandemic as an example. The attempt is, through the description of the main strategies that this specific branch of communication developed after having spread after the attack on the Twin Towers in New York on 11 September 2001, to hypothesize a further risk communication strategy that could be effective in particular in the case of health risk. This integrated communication model not only takes into account the integration between risk communication and crisis communication but also two additional aspects necessary in case of health risk: on one hand, the informative aspect, and on the other hand the aspect defined persuasive / preventive / participatory.